Structural framework and timing of the Pahtohavare Cu ± Au deposits, Kiruna mining district, Sweden - L. Logan; E. Veress; J. B. H. Andersson; O. Martinsson; T. E. Bauer (Solid Earth, 2023)
As part of the larger mineral systems approach to Cu-bearing mineralization in northern Norrbotten, this study utilizes structural geology to set the classic Pahtohavare Cu ± Au deposits into an up-to-date tectonic framework. The Pahtohavare Cu ± Au deposits, situated only 5 km southwest of the Kiirunavaara world-class iron oxide–apatite (IOA) deposit, have a dubious timing, and their link to IOA formation is not constrained. The study area contains both epigenic Cu ± Au (Pahtohavare) and iron oxide–copper–gold (IOCG; Rakkurijärvi) mineral occurrences which are hosted in bedrock that has been folded and bound by two shear zones trending northeast to southwest and northwest to southeast to the east and southwest, respectively. Structural mapping and petrographic investigation of the area reveal a noncylindrical, SE-plunging anticline. The cleavage measurements mirror the fold geometry, which characterizes the fold as F2 associated with the late phase of the Svecokarelian orogeny. Porphyroclasts with pressure shadows, mylonitic fabrics, and foliation trails in porphyroblasts indicate S0/S1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="32pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="b8ca7c5c7b58ce68d187b84a9dc9005e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="se-14-763-2023-ie00001.svg" width="32pt" height="14pt" src="se-14-763-2023-ie00001.png"/></svg:svg> is a tectonic fabric. The epigenetic Pahtohavare Cu ± Au mineralization sits in brittle–ductile structures that cross-cut an earlier foliation and the F2 fold, indicating that the timing of the deposits occurred syn- to post-F2 folding, at least ca. 80 Myr after the Kiirunavaara IOA formation. A 3D model and cross-sections of the Pahtohavare–Rakkurijärvi area and a new structural framework of the district are presented and used to suggest that the shear zones bounding the area are likely reactivated early structures that have played a critical role in ore formation in the Kiruna mining district.